Bencana Alam Perspektif Al-Qur’an Analisis Kisah Nabi Nuh, Nabi Hud dan Nabi Luth (Kajian Tematik) - Alizaky Alizaky (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2020)
Disasters often afflict humans, in various forms, including hurricanes, earthquakes, floods and others. Incidents like this have happened in the past when the people were told in many verses of the Qur’an, in general this is usually closely related to the defiance of the previous ummah against the messengers of Allah SWT, immoral acts and worshiping other than Allah SWT, that means there is the relationship of every disaster that comes with human disobedience to Allah SWT. So from these problems, the writing of this thesis aims to find out